Quantification of Human Oral and Fecal Streptococcus parasanguinis by Use of Quantitative Real-Time PCR Targeting the groEL Gene - Chen, Qiurong; Wu, Guojun; Chen, Hui; Li, Hui; Li, Shuo; Zhang, Chenhong; Pang, Xiaoyan; Wang, Linghua; Zhao, Liping; Shen, Jian (Frontiers in Microbiology, 2019)
Two pairs of species-specific PCR primers targeting the housekeeping groEL gene, Spa146f-Spa525r and Spa93f-Spa525r, were designed to quantify human oral and fecal Streptococcus parasanguinis. Blast analysis against reference sequences of NCBI nucleotide collection database and the Chaperonin Sequence Database showed the forward primers Spa146f and Spa93f 100% matched only with S. parasanguinis, and the in silico Simulated PCR algorithm showed both primer pairs hit only S. parasanguinis groEL gene in Chaperonin Sequence Database. The two primer pairs were respectively used to perform PCR with saliva DNA of each of 6 human subjects, and the amplicons of individual PCR reactions were cloned. The phylogenetic analysis showed cloned sequences were all affiliated to S. parasanguinis, which further validates the specificity of two primer pairs, and that individual subjects harbored multiple genotypes of S. parasanguinis in saliva. By spiking S. parasanguinis into human fecal samples, we found the quantification limit of quantitative real-time PCR (qPCR) assays for both primer pairs was 5 to 6 log10 groEL copies/g feces. Human fecal S. parasanguinis amounts quantified with qPCR using each of the two primer pairs correlated well with those determined with metagenomic sequencing. qPCR with either primer pair showed periodontitis patients had significantly lower level of saliva S. parasanguinis than healthy people. In both feces and saliva, the S. parasanguinis abundances quantified with two primer pairs exhibited strong and significant correlation. Our results show that the two S. parasanguinis-specific primer pairs can be used to quantify and profile human saliva and fecal S. parasanguinis.